2019
DOI: 10.1111/bjdp.12302
|View full text |Cite
|
Sign up to set email alerts
|

Some but not all aspects of (advanced) theory of mind predict loneliness

Abstract: Children's (advanced) theory of mind (AToM) has been related to numerous real‐world social consequences, including regarding their feelings of loneliness. A recent study has shown that AToM does not rely on a single underlying ability, instead involving three distinct factors: social reasoning, reasoning about ambiguity, and recognizing transgressions of social norms. The present study of 229 5‐ to 8‐year‐olds investigated whether and how these three aspects of AToM cognition are related to children's feelings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Such an interpretation would fit with Devine and Hughes' results (Devine & Hughes, 2013), which showed an association between low ToM skills and high peer rejection in 8‐ to‐13‐year‐old boys and low ToM skills and high loneliness in 8‐ to‐13‐year‐old girls. The link between ToM and loneliness is further confirmed by Koerber and Osterhaus (2019), who found social reasoning (but not ambiguity nor recognising transgressions of social norms) to be related to perceived loneliness among 5‐ to 8‐year‐olds, and by putting together the results of two longitudinal studies conducted with community children. The first one found that ToM ability at 5 years old predicts friendlessness 2 years later (Fink, Begeer, Peterson, Slaughter, & de Rosnay, 2015).…”
Section: Tom In Middle Childhoodsupporting
confidence: 55%
See 1 more Smart Citation
“…Such an interpretation would fit with Devine and Hughes' results (Devine & Hughes, 2013), which showed an association between low ToM skills and high peer rejection in 8‐ to‐13‐year‐old boys and low ToM skills and high loneliness in 8‐ to‐13‐year‐old girls. The link between ToM and loneliness is further confirmed by Koerber and Osterhaus (2019), who found social reasoning (but not ambiguity nor recognising transgressions of social norms) to be related to perceived loneliness among 5‐ to 8‐year‐olds, and by putting together the results of two longitudinal studies conducted with community children. The first one found that ToM ability at 5 years old predicts friendlessness 2 years later (Fink, Begeer, Peterson, Slaughter, & de Rosnay, 2015).…”
Section: Tom In Middle Childhoodsupporting
confidence: 55%
“…However, we do not know whether specific aspects of ToM were particularly enhanced by the training programme. As argued by Koerber and Osterhaus (2019), not all aspects of advanced ToM predict loneliness. Therefore, future studies will clarify which mental circuits or pathways are more connected with social skills, in order to build targeted interventions.…”
Section: Discussionmentioning
confidence: 92%
“…In particular, children begin to acquire morecomplex forms of false-belief understanding (Perner & Wimmer, 1985), they become more proficient in interpreting complex social situations (Baron-Cohen, O'Riordan, Stone, Jones, & Plaisted, 1999;Bosacki & Astington, 1999;Devine & Hughes, 2013;Happé, 1994), and they improve their ability to interpret mental states and emotions from facial expressions (Baron-Cohen, Wheelwright, Hill, Raste, & Plumb, 2001). Many of these aspects of advanced ToM (AToM) are closely linked to children's social competences, including feelings of loneliness or the ability to form friendships (Bosacki, Moreira, Sitnik, Andrews, & Talwar, 2020;Caputi, Cugnata, & Brombin, 2020;Devine, White, Ensor, & Hughes, 2016;Fink, Begeer, Peterson, Slaughter, & de Rosnay, 2015;Koerber & Osterhaus, 2020;Slaughter, Imuta, Peterson, & Henry, 2015). Despite its relevance for children's everyday experiences, there is a paucity of longitudinal work that narrowly tracks the development of AToM in middle childhood across multiple time points and over extensive periods of time.…”
mentioning
confidence: 99%
“…The validity of the RMET as a measure of advanced ToM skills (e.g. higher-order mental state reasoning, Koerber & Osterhaus, 2019) is supported by studies that report significant correlations with conceptually similar measures such as the Faces subtest of the Cambridge Mindreading Face-Voice Battery for Children (r = .35, p < .01; Golan et al, 2015). Adequate internal consistency has been reported with young adolescents (Goldstein & Winner, 2012) and good test-retest stability (inter-correlation = .833), was found with the Italian version of the RMET (Vellante et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The affective theory of mind which involves the ability to recognise or identify emotions in others (Wellman, 2020), develops in young children by the age of four and enables one to make sense of themselves and others in terms of thoughts and emotions (Wellman, 2020). This social skill becomes valuable to help adolescents carve out an identity for themselves (Białecka-Pikul et al, 2020), forming and maintaining peer relationships (Koerber & Osterhaus, 2019). For example, some studies show adolescents who prefer solitude reported higher levels of perspective-taking, irony understanding, emotion recognition, and self-conscious emotions (Mewhort-Buist & Nilson, 2020;Muris & Broeren, 2009).…”
Section: Theory Of Mind and Self-perceptionsmentioning
confidence: 99%